P 65 Navigated repetitive transcranial magnetic stimulation – therapeutic use in early rehabilitation treatment after stroke. Issue 10 (October 2017) - Wedekind, C.; Weber, H.; Rieckmann, P.
Abstract : Background: MRI navigated repetitive transcranial magnetic stimulation (nTMS) provides a new tool for neuromodulation – we report on its effects on recovery of brain function in a setting of inpatient rehabilitation early after stroke. Methods: MRI based nTMS (inhibitory stimulus paradigm, 900 pulses at an intensity of 110% motor threshold, applied at 1 Hz) oft the contralesional primary motor cortex. Each patient participated in a median of 7 stimulation sessions, 3 sessions per week. Each stimulation session was followed by an immediate session of physical therapy, logopedic or ergotherapeutic treatment. Results: A total of 27 cases were subject to at least 3 nTMS sessions (range 3–19 sessions) in addition to the standard multimodal therapeutic setting. The vast majority of cases experienced an improvement of motor deficit, neglect and dysphagia. The activities of daily life (Barthel) index increased from 15 to 30 points median. Two thirds of the patients were enabled to continue rehabilitation in phase C. Adverse events did not occur. Conclusions: The application of nTMS for early rehabilitation purposes in stroke patients is safe and effective. It appears to uncover a regeneration potential still hidden. Thus it may become a useful therapeutic adjunct to the standard multimodal approach.